專利侵權損害賠償之實證研究 Empirical Study on Damage Award of Patent Disputes - 吳靜怡 Ching-Yi Wu (Kējì Fǎxué Pínglùn, 2014)
本文旨在比較中美兩國法制就專利侵權損害賠償範圍及其計算方法之異同，探討兩國法院判決之損害賠償金額是否均適度足夠。首先，以經濟觀點說明專利侵權損害賠償金額之計算與若非侵權的but for 世界之經濟基礎不能脫勾的理由，再淺介美國專利侵權損害賠償之法律規定及重要案例，輔以該國學者對此議題所為之實證研究，而以美國聯邦貿易委員會（The Federal Trade Commission, FTC）在專利改革中所提出之檢討及建言做小結。其後，簡單說明我國專利侵權損害賠償之法律規定；實證研究方面，係以2008 年7月1 日起至2014 年4 月30 日止智慧財產法院有關專利侵權損害賠償之一審判決為研究對象，先以敘述統計方式量化研究專利權人之「勝訴率」、「判賠率」、「判賠金額大小」、「各種損害賠償範圍之採用比率」、「懲罰性損害賠償酌定之比例」等資料，以敘述統計方式，說明目前智財法院對於專利侵權損害賠償案件之判決情形；再詳細閱讀前揭研究範圍內關於判決專利權人勝訴並給予損害賠償之一審判決內容，以質性說明量化研究之成果，並整理歸納出「智財法院一審判決損害賠償金額不如專利權人預期之理由」、 「智財法院判決損害賠償金額偏低之理由」、「同業利潤標準採用與否之轉變」以及「整體市場價值法則之應用」等各點，希望能以實證方式驗證各種假說之正確性、重新建構專利侵權之損害賠償範圍並提出檢討，而有助於專利侵權救濟制度之健全發展。 The purpose of this study was to compare the scope of damage compensation and calculations regarding patent infringement between the laws of ROC and America as well as to discuss whether the damage compensation amounts determined by these two countries are sufficient. First of all, it explained that the calculation of damage compensation regarding patent infringement cannot be separated from the but for world (non-infringement world) economy from the economic perspective. Then it briefly introduced the statutory laws and case laws for damage compensation related with patent infringement in America, incorporated with the empirical researches made by American scholars aiming at this issue. Meanwhile, the summary was made against the review and recommendations proposed by the Federal Trade Commission (FTC) to the patent reform. After that, the relief system for patent infringement and legal basis of damage compensation derived from infringement were explained in brief. As to the empirical research, the subjects were judgments of first instance made by intellectual property court for damage compensations in related with patent infringement from July 1, 2008 until April 30, 2014. It first quantified the “winning rate,” “percentage of damage award,” “compensation amount,” “awarded percentages for various scopes of damage compensation,” and “awarded ratio for punitive damage compensation” via descriptive statistics to explain the judgments made by intellectual property court aiming at damage compensation in related with patent infringement. Following, the judgments of first instance awarded to the patent owners and their damage compensations in preceding research were read carefully to explain the quantitative results via qualitative description and summarized that the reasons why the damage compensation amount made by intellectual property court in first instance was less than the one expected by the patent owner; the reason for relatively low compensation amount determined by intellectual property court; the change of whether to adopt the profit standards in the same industry, and as well as the application of the entire market value rule. It is expected to verify the correctness of various assumptions via empirical approaches and facilitate the sound development of relief system in related with patent infringement.